Reconfigurable localization for AUVs based on Time of Arrival of encoded acoustic signals - Tiago Coelho Brandão Pinto (2019)
Develop a system capable of switching between different localization techniques. Concretely, conceive a system (on FPGA) capable of alternating between a localization based on BPSK and QPSK signal modulations. This way, the system can take advantage of the different characteristics the different encodings offer.Simultaneously, study the usage of the Hilbert Transform to better estimate the Time of Arrival of the encoded acoustic signals.